The credibility of central bank announcements - Marco Hoeberichts (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
In this paper, we present a monetary policy game in which the central bank has a private forecast of supply and demand shocks. The public needs to form its inflationary expectations and can make use of central bank announcements. However, because of the credibility problem that the central bank faces, the public will not believe a precise announcement. By extending the arrangement proposed by Garfinkel and Oh (1995) to a model that includes private information about both demand and supply shocks, we investigate the feasibility of making imprecise credible announcements concerning the rate of inflation.
urn:nbn:de:hebis:30-9992
Keywords: E52; E58; 330; monetary policy; private information; announcements